Optimizing On-Time Delivery Performance through Lean and QCDSM Framework in the Procurement Process of PT Lautan Air Indonesia - Angga Widyaswara; Abby Yazid Bustommy (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to optimize the performance of on-time delivery in the procurement process at PT Lautan Air Indonesia, where delivery delays reach 23% and significantly disrupt the reliability of the supply chain. On-time delivery is an important indicator of operational performance, reflecting the accuracy of planning, vendor collaboration, and supply chain execution. Persistent delays in the procurement process not only increase operational costs but also pose a risk to customer confidence and production continuity. Materials and methods. This research applies an integrative approach that combines Lean Thinking, Root Cause Analysis (RCA), and QCDSM (Quality, Cost, Delivery, Safety, Morale) framework. Lean Thinking is used to identify wastes such as waiting and delays, RCA to determine the root cause of procurement delays, and QCDSM to evaluate overall improvements. The study was conducted in the Procurement Division (MNT) of PT Lautan Air Indonesia, with data analyzed quantitatively by comparing the percentage of delays before and after corrective actions. Result. The findings reveal that the root causes of delays are vendors not responding to purchase orders, lack of reminder features in SAP systems, and manual purchase order processing. After implementing corrective measures such as SAP-based monitoring, automated reminders, and automated delivery purchase orders, the delay rate decreased significantly from 23% to 9.99%. The QCDSM evaluation showed improvements in all dimensions: higher data quality, reduced idle costs, improved delivery reliability, reduced operational risk, and improved team morale. Conclusion. The integration of Lean, RCA, and QCDSM has proven to be an effective and comprehensive approach in reducing procurement delays. The study contributes to both academic and practical fields by filling research gaps in combining Lean and QCDSM for improved procurement performance, while providing a workable model for companies facing similar challenges in their supply chains